#TITLE_ALTERNATIVE# - Adriansyah (NIM 107 03 035), Edwin
Abstrac: BHA (3-tersier-butil-4-hydroksianisol), BHT (2,6-di-tersier-butil-4-metilfenol), and TBHQ (2-tersier-butilbenzena-1,4-diol) are widely used as phenolic antioxidants in different foods, cosmetics, and pharmaceuticals products with high oil content. Reactivity and stability of these compound were studied by PM3 semi-empirical quantum mechanic methods using Hyperchem (version 7.51) as software. Minimum energy, molar refractivity (MR), surface area, and gap HOMO-LUMO energy were used to evaluate the reactivity of the compund, while minimum energy from energy optimation were used to evaluate their stability. The minimum energy, molar refractivity, and gap HOMO-LUMO energy of TBHQ were respectively -45860,5891 kkal/mol, 52,074 ?, and 48,825 e.V, while the minimum energy from energy optimation of BHT was -55947,3073 kkal/mol. The results showed that TBHQ has the highest reactivity whereas BHT has the highest stability.